Avalanche Multiplication Noise in GaN p–n Junctions Grown on Native GaN Substrates. Issue 2 (30th October 2019) - Cao, Lina; Ye, Hansheng; Wang, Jingshan; Fay, Patrick
Abstract : GaN p–n junction diodes grown on native GaN substrates have been fabricated and characterized. The devices exhibit a positive temperature coefficient of breakdown obtained from variable temperature current–voltage measurements, confirming the impact ionization avalanche. The low‐frequency noise characteristics of these devices have been measured under forward and reverse bias conditions. The forward bias noise spectra are dominated by the 1/ f noise, and the current spectral density is proportional to I 1.6 . Under reverse bias, the noise spectra show 1/ f noise at reverse biases below the avalanche threshold. However, at reverse biases in the avalanche regime, the multiplication noise overwhelms the 1/ f noise, resulting in a white noise spectrum. To further characterize the avalanche process, the excess noise factor, F, is obtained from the measured noise spectra of diodes biased in reverse avalanche. For the case of pure hole injection (achieved by incorporating a thin pseudomorphic In0.07 Ga0.93 N layer at the cathode of the device and illuminating with 390 nm UV light), a low excess noise factor is achieved. The impact ionization ratio α / β extracted from the multiplication noise ranges from 0.07 to 0.38 over the electric field ranging from 2.8 to 3.7 MV cm −1, consistent with the impact ionization coefficients reported previously using the photomultiplication method. Abstract : The low‐frequency noise of GaN p–n junctions grown on GaN substrates is characterized. The forward bias noise spectra are predominantly 1/ f, whereas in reverse bias the devices exhibit white noise in avalanche. The excess noise factor F and impact ionization ratio α / β are extracted from the noise; F < 1 is obtained, indicating the promise of GaN‐based devices for low‐noise applications.